Correlation between Self-Efficacy and Mathematical Argumentation: A Case Study of Mathematics Education Students - Jagadianti, Gurit Wulan; Wijayanti, Pradnyo (Universitas Negeri Surabaya, 2024)
Self-efficacy in the context of mathematical argumentation describes the importance of understanding an individual's belief in forming solid argumentation skills. Mathematical argumentation helps individuals present various opinions to support creative mathematical solutions. This research aims to determine the correlation between self-efficacy and mathematical argumentation among students in the mathematics education program. This study employs a quantitative correlational approach using survey methods to collect data from 41 students in the mathematics education program. Data was obtained from a self-efficacy questionnaire and statistical-related mathematics tasks that assessed students' mathematical argumentation. Based on the research findings, no correlation was found between self-efficacy and mathematical argumentation. Students with high self-efficacy do not always have strong mathematical arguments, and vice versa. The level of self-efficacy in students does not determine the strength of the mathematical arguments presented by students.